The Power of a Modern Soundtrack: Exploring the Musical Legacy of Luhrmann’s Romeo + Juliet (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2025)
This piece analyzes Baz Luhrmann's Romeo + Juliet film and how its soundtrack contributed to the film's popularity and the original Shakespeare story. In order to understand the cultural legacy of the film and its music, I analyzed TikTok videos and film reviews to understand how young people in the 1990s and today engage with the film and Shakespeare.For additional context, listen to the author's reflection on the piece below.